2021
DOI: 10.1186/s12989-021-00409-y
|View full text |Cite
|
Sign up to set email alerts
|

Respirable stone particles differ in their ability to induce cytotoxicity and pro-inflammatory responses in cell models of the human airways

Abstract: Background Respirable stone- and mineral particles may be a major constituent in occupational and ambient air pollution and represent a possible health hazard. However, with exception of quartz and asbestos, little is known about the toxic properties of mineral particles. In the present study, the pro-inflammatory and cytotoxic responses to six stone particle samples of different composition and with diameter below 10 μm were assessed in human bronchial epithelial cells (HBEC3-KT), THP-1 macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 80 publications
5
52
0
4
Order By: Relevance
“…As for α-quartz, exposure to anorthosite, rhomb porphyry or quartz diorite particles in combination with DEP B0 induced significant increases in the secretion of pro-inflammatory cytokines and expression of genes related to inflammation and redox responses compared with exposure to the individual particle samples. The potency of the mineral samples in combination with DEP B0 was mostly in line with the order of potency reported for the individual samples in previous studies using the same cell model, with α-quartz being the most potent followed by anorthosite, while rhomb porphyry and quartz diorite induced lower and similar levels [ 48 ]. Considering that the anorthosite does not contain any quartz (Additional file 3 : Table S1) [ 48 ], these results clearly show that the increased effects of combined exposure cannot be explained by quartz content alone, suggesting that other mineral components are important.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…As for α-quartz, exposure to anorthosite, rhomb porphyry or quartz diorite particles in combination with DEP B0 induced significant increases in the secretion of pro-inflammatory cytokines and expression of genes related to inflammation and redox responses compared with exposure to the individual particle samples. The potency of the mineral samples in combination with DEP B0 was mostly in line with the order of potency reported for the individual samples in previous studies using the same cell model, with α-quartz being the most potent followed by anorthosite, while rhomb porphyry and quartz diorite induced lower and similar levels [ 48 ]. Considering that the anorthosite does not contain any quartz (Additional file 3 : Table S1) [ 48 ], these results clearly show that the increased effects of combined exposure cannot be explained by quartz content alone, suggesting that other mineral components are important.…”
Section: Discussionsupporting
confidence: 86%
“…Based on these results, the concentrations of 25 and 50 µg/mL DEP (2.6 and 5.3 μg/cm 2 ) were chosen for the combination experiments. The concentrations of 25, 50 and 100 μg/mL α-quartz (2.6, 5.3 and 10.5 μg/cm 2 ) were chosen based on previous experiments published elsewhere [ 48 ]. A cytokine-binding assay was also performed to assess whether non-specific binding of cytokines to DEP may have interfered with the measurements [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IPA analysis indicated that IL-1, IL-6, and TNF-a were among the chief regulators for predicted pathways mediating cSiO 2triggered inflammatory proteins and that these pathways were downregulated by DHA. cSiO 2 instillation into the lung is wellknown to acutely elicit secretion of proinflammatory cytokines such as IL-1b, IL-1a, IL-6, and TNF-a by direct or indirect action on alveolar macrophages, neutrophils, and epithelial cells (40)(41)(42)(43). Therefore, it was surprising that cSiO 2 's effects on these proinflammatory cytokines in BALF were modest across the time cohorts of this study.…”
Section: Discussionmentioning
confidence: 80%